The Long-Term Clinical and Economic Impact of Universal Varicella Vaccination in Slovenia - Colleen Burgess; Stephanie Kujawski; Ajda Lapornik; Goran Bencina; Manjiri Pawaskar (Journal of Health Economics and Outcomes Research)
**Background:** Despite the substantial burden of varicella infection, Slovenia does not currently have a universal varicella vaccination (UVV) program. We modeled the long-term clinical and economic impact of implementing 2-dose UVV strategies compared with no vaccination in Slovenia. **Methods:** A previously published dynamic transmission model was adapted to the demographics, varicella seroprevalence, herpes zoster incidence, and contact patterns in Slovenia. Six 2-dose UVV strategies, vs no vaccination, were considered over a 50-year period, including monovalent vaccination (Varivax^®^ [V-MSD] or Varilrix^®^ [V-GSK]) at ages 12 and 24 months, or monovalent vaccination at 15 months followed by monovalent or quadrivalent vaccination (ProQuad^®^ [MMRV-MSD] or Priorix- Tetra^®^ [MMRV-GSK]) at 5.5 years. Costs, quality-adjusted life-years, and incremental cost-effectiveness ratios vs no vaccination were calculated to assess the economic impact of each strategy from payer and societal perspectives. **Results:** The incidence of varicella infection was estimated as 1228 per 100 000 population in the absence of UVV. Over 50 years, depending on vaccination strategy, UVV reduced varicella cases by 77% to 85% and was associated with substantial reductions in varicella deaths (39%-44%), outpatient cases (74%-82%), and hospitalizations (74%-82%). The greatest reductions were predicted with V-MSD (15 months/5.5 years) and V MSD/MMRV-MSD (15 months/5.5 years). **Discussion:** All 2-dose UVV strategies were cost-effective compared with no vaccination from payer and societal perspectives, with V-MSD (15 months/5.5 years) being the most favorable from both perspectives. **Conclusion:** Policymakers should consider implementing UVV to reduce the burden of varicella disease in Slovenia.